On averaging of nonlinear elliptic problems with inhomogeneous boundary conditions - Skrypnik, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
A sequence of solutions of nonlinear elliptic problems is considered in the case where the Dirichlet conditions are given on the one part of the boundary and the Neumann conditions are given on the other part. The boundary-value problem is constructed.